Number the stars - Lowry, Lois. (New York : Bantam Doubleday Dell Books for Young Readers, 1998)
In 1943, during the German occupation of Denmark, ten-year -old Annemarie learns how to be brave and courageous when she helps shelter her Jewish friend from the Nazis.
670
Keywords: World War, 1939-1945 -- Denmark -- Juvenile fiction; World War, 1939-1945 -- Denmark -- Fiction; World War, 1939-1945 -- Jews -- Rescue -- Fiction; Friendship -- Fiction; Denmark -- Fiction